WEBSITE BASED EMPLOYEE ACCEPTANCE INFORMATION SYSTEM AT PT NOTO TEKNOLOGI INDONESIA - lasmedi afuan; Nurul Hidayat; Bangun Wijayanto; Indah Cahya Febriani (Informatika, Universitas Jenderal Soedirman, 2022)
The development of information technology is currently growing very rapidly, many companies want to improve their work processes by using information systems to process company data more quickly and efficiently. The process of accepting prospective employees at PT Noto Teknologi Indonesia is still done manually, i.e. prospective employees must register and deliver job application files to the office. To find out the results of the selection of employee recruitment, prospective employees still get information via WhatsApp. This makes the acceptance of new employee candidates less effective and efficient because it will take a lot of time and the possibility of data errors. So in this study a website based recruitment information system was created to facilitate the process of accepting new employees. The method used in making this system is the waterfall method where this method has 5 stages, namely user needs analysis, system design, implementation, testing and maintenance by PT Noto Teknologi Indonesia. The results of the black-box test show valid results for all features which indicate that this system is as expected. From the results of black-box testing, it can be concluded that this system is feasible to use as a tool to facilitate the process of accepting new employees at PT Noto Teknologi Indonesia.